2003
DOI: 10.1002/jcla.10108
|View full text |Cite
|
Sign up to set email alerts
|

Chitotriosidase activity in plasma and mononuclear and polymorphonuclear leukocyte populations

Abstract: In the general population, about 5% of individuals are homozygotic and 35% are heterozygotic carriers for chitotriosidase (ChT) deficiency. Activated macrophages are considered to be the main source of plasma ChT activity, which permits the biochemical characterization of homozygote deficients. However, in the case of detecting heterozygotic carriers, the results are often inconclusive. The activities of ChT in plasma and mononuclear (MN) and polymorphonuclear (PMN) leukocytes were determined in 169 control su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 17 publications
4
32
0
Order By: Relevance
“…In the course of an appropriate stimulus, this enzyme is secreted from the granules of macrophages and polymorphonuclear leukocytes [33][34][35][36]. Having assessed the ChT levels in cord blood, our study showed no significant difference between the NVD and C/S groups.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In the course of an appropriate stimulus, this enzyme is secreted from the granules of macrophages and polymorphonuclear leukocytes [33][34][35][36]. Having assessed the ChT levels in cord blood, our study showed no significant difference between the NVD and C/S groups.…”
Section: Discussionmentioning
confidence: 56%
“…Its primary source is activated macrophages [7]. Following an appropriate stimulus, this enzyme can either be secreted by macrophages or by polymorphonuclear leukocytes [8]. It was first defined in patients with Gaucher disease, and was found be increased 1000-fold in macrophages of the tissues of Gaucher patients [9].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, increased ChT levels are also reported in thalassemia, malaria and systemic candidiasis (36,37 (Fig. 1); these levels were decreased to significantly lower levels with therapy (Fig.…”
Section: F I G U R E 5 De Mo N S T R a T I O N O F T H E D I F F E mentioning
confidence: 61%
“…In as study conducted on brucellosis patients, Akbulut et al reported an amelioration of serum NPT values which were found to be significantly higher before treatment (35 (11,36). Moreover, increased ChT levels are also reported in thalassemia, malaria and systemic candidiasis (36,37 (Fig.…”
Section: F I G U R E 5 De Mo N S T R a T I O N O F T H E D I F F E mentioning
confidence: 91%
“…Nonetheless, physiological conditions such as ageing have also been found to correlate with a progressive increase of plasmatic Chit activity. 17,18 This might suggest that the innate immune system is involved in protecting the healthy human organism from cell damage that occurs during ageing, perhaps linked to oxidative processes. 19 Given its peculiar immune 'privilege', healthy central nervous system (CNS) status is tightly regulated and maintained at a low functional level in order to prevent immune-mediated damage from occurring.…”
Section: Chit Chitin and The Central Nervous Systemmentioning
confidence: 99%